[Cu(Nn1)2]Clo4, a Copper (I) Complex as an Antimicrobial Agent for the Treatment of Piscirickettsiosis in Atlantic Salmon - Guerrero-Nunez, J; Guerrero-Nunez, J; Modak-Canobra, B; Tello-Reyes, M; Soto-Aguilera, S; Arce-Ortega, P; Arce-Ortega, P; Vargas-Cardenas, R; Aldabaldetrecu-Urbieta, M; Aldabaldetrecu-Urbieta, M; Parra-Mardonez, N (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Piscirickettsia salmonis is the pathogen that most affects the salmon industry in Chile. Large quantities of antibiotics have been used to control it. In search of alternatives, we have developed [Cu(NN1)2]ClO4 where NN1 = 6-((quinolin-2-ylmethylene)amino)-2H-chromen-2-one. The antibacterial capacity of [Cu(NN1)2]ClO4 was determined. Subsequently, the effect of the administration of [Cu(NN1)2]ClO4 on the growth of S. salar, modulation of the immune system and the intestinal microbiota was studied. Finally, the ability to protect against a challenge with P. salmonis was evaluated. The results obtained showed that the compound has an MIC between 15 and 33.9 μg/mL in four isolates. On the other hand, the compound did not affect the growth of the fish; however, an increase in the transcript levels of IFN-γ, IL-12, IL-1β, CD4, lysozyme and perforin was observed in fish treated with 40 μg/g of fish. Furthermore, modulation of the intestinal microbiota was observed, increasing the genera of beneficial bacteria such as Lactobacillus and Bacillus as well as potential pathogens such as Vibrio and Piscirickettsia. Finally, the treatment increased survival in fish challenged with P. salmonis by more than 60%. These results demonstrate that the compound is capable of protecting fish against P. salmonis, probably by modulating the immune system and the composition of the intestinal microbiota. © 2024 by the authors.